Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The Question:

Let a,b,c be complex numbers satisfying $abc = 1$ and $a+b+c =$ $\frac1a + \frac1b + \frac 1c$ Show that at least one of $a,b,c$ must equal $1$.

What I have tried: Rearranging the $RHS$ and subbing in the first equation we get $a+b+c = bc + ac+ab$

Now from Equation 1 we have $ a = \frac{1}{bc}$ and subbing this into the manipulation above we get $\frac{1}{bc} + b+c = bc + \frac 1b + \frac 1c$

Now multiplying out by $bc$ we get $1+b+c = (bc)^2 +c + b$ implying that $(bc)^2 = 1$ And from equation one we get $a^2b^2c^2 = 1^2 = 1$ and $b^2c^2 = 1$ therefore $a^2 = 1$ and $a = 1$.

Is this correct/sufficient if not can you point me in the right direction and feel free to show other methods etc. Thanks.

share|cite|improve this question
"Now multiplying out by $bc$ we get" Are you sure we get that? – Nameless Dec 29 '12 at 21:04
Ah, let me re-work thanks! – fosho Dec 29 '12 at 21:05
Also note that, because you are working with complex numbers, you cannot assume, in this context, that square roots are positive. – Mark Bennet Dec 29 '12 at 21:15
up vote 6 down vote accepted

Let $s=a+b+c = bc + ac+ab$.

Then $a,b,c$ are the roots of

$$(X-a)(X-b)(X-c)=X^3-(a+b+c)X^2+(ab+ac+bc)X-abc$$ $$=X^3-sX^2+sX-1$$

Now all you have to do is observe that $X=1$ is a root of $X^3-sX^2+sX-1$.

share|cite|improve this answer
+1 This is the neat way that probably occurs to the more "mature" visitors who were taught all this stuff at school? – Old John Dec 29 '12 at 21:09
Yes, when you reach a certain level, all problems of symmetric polynomials suggest this sort of approach :) – Thomas Andrews Dec 29 '12 at 21:11
I have always thought this an elegant way of looking at such problems - however it does not always work as well as this. One indications for using this approach is that all the given equations are symmetric. – Mark Bennet Dec 29 '12 at 21:12

Alternatively, you can just write:

$$(a-1)(b-1)(c-1)=abc - (ab+ac+bc) + (a+b+c) -1 = 1 - [ab+ac+bc-(a+b+c)] - 1 = 0$$

So one of $a-1,b-1,c-1$ must be zero.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.